Improved heart rate variability in postmenopausal women following short-term combined exercise training - Rizky Prayuda Putra; Helga Anindya Mubarok; Nathania Elma Fithriyah; Dani Rahmat Ramadhana; Gadis Meinar Sari; Tri Hartini Yuliawati; Raden Argarini (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Imbalances in cardiac autonomic nervous systems are associated with cardiovascular risk factors and poor cardiac outcomes. Heart rate variability (HRV) is a practical and reproducible measure of cardiac autonomic nervous system function. Exercise training promotes positive adjustments in HRV. However, previous studies have reported mixed results. Therefore, this study aimed to investigate the effects of short-term combined exercise training on heart rate variability in post-menopausal women. Thirty-four women aged 50-80 years, at least 12 months post-menopause, were divided into a control (CON) group and an exercise (EX) training group. The participants in the exercise group underwent a 2-week of combined exercise program consisting of aerobic, strength, flexibility, and balance exercises. HRV was recorded using an Actiheart device, before and after the final exercise intervention in a sitting position. The significant main effects of time and group were found in the parameter of SDNN (p time = 0.039; p group = 0.026). Post-hoc analysis showed a borderline increase in SDNN in the EX group (POST: 48.79 ± 17.88 VS 44.54 ± 17.39, p = 0.055). No significant change was observed in the CON group (POST: 35.55 ± 13.51 VS 33.17 ± 8.74, p = 0.288). Statistical analysis of other HRV components revealed no significant results (all P > 0.05). In conclusion, a 2-week of combined exercise training program, including aerobic, resistance, balance, and flexibility exercises improves global cardiac autonomic function in post-menopausal women.